DESIGN OF BORED PILE FOUNDATION, RETAINING WALL, AND DRAINAGE SYSTEM CREATIVE DIGITAL OFFICE SOUTH JAKARTA - Zukhal Abror, Farras
Creative Digital Office is an office building built at Setiabudi Tengah 2 street, Setiabudi, South Jakarta. The office design consists of 6 floors and 1 basement floor as a parking lot. This final project aims to design a foundation system that can support the load from the superstructure, retaining wall that is able to support lateral earth pressure and provide safety for the basement excavation, and drainage system that can channel the rainwater thet enters the project area into into road drainage channel existing. The design of retaining wall aims to accommodate the lateral earth forces and provide safety for the basement excavation as deep as 3 meters. The type of retaining wall used is a counterfort wall with 4 meters depth and a base of 2,8 meters. This counterfort wall reinforcement has 0,2 meters of thickness with 2 meters distances between the reinforcement. The analysis and modeling of counterfort wall was calculated using PLAXIS 2D through staged construction. The analysis was carried out to obtain internal forces, lateral deflection, and safety factor of each staged constructions. The foundation used in this project is bored pile foundation with a diameter of 0,8 meters and depth of 25 meters. The analysis was carried out by determining the axial bearing capacity of single pile manually, lateral bearing capacity using LPILE, group bearing capacity using GROUP, settlement analysis manually, and reinforcement using SPCol. In addition, pile cap design consists of 3 types of thickness namely 1 meter, 1,2 meter, and 1,5 meter which are modelled using SAFE. The drainage system is designed using a sump pit as a pump and a U-Ditch channel to drain the rainwater to the sump pit for pumping. In this project, 2 sump pits and U-Ditch channel are planned with a width of 0,3 meter and height of 0,4 meter.